2013
DOI: 10.1088/0004-637x/768/1/22
|View full text |Cite
|
Sign up to set email alerts
|

Connection Between Mid-Infrared Emission Properties and Narrow-Line Region Outflows in Type 1 Active Galactic Nuclei

Abstract: The location of warm dust producing the Mid-infrared (MIR) emission in Type 1 Active Galactic Nuclei (AGNs) is complex and not yet fully known. We explore this problem by studying how the MIR covering factor (CF MIR = L MIR /L bol ) correlates with the fundamental parameters of AGN accretion process (such as L bol , black hole mass M BH , and Eddington ratio L/L Edd ) and the properties of narrow emission lines (as represented by [O III] λ5007), using large data sets derived from the Sloan Digital Sky Spectros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…In a forthcoming paper, we perform similar studies using BAL quasars (S. Zhang et al 2013 in preparation) and find significant correlations of β NIR with the velocities and absorption strength of BALs, in good agreement with the results presented here. One important question arises as to how the outflows relate to the hot dust in quasars.…”
Section: Summary and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a forthcoming paper, we perform similar studies using BAL quasars (S. Zhang et al 2013 in preparation) and find significant correlations of β NIR with the velocities and absorption strength of BALs, in good agreement with the results presented here. One important question arises as to how the outflows relate to the hot dust in quasars.…”
Section: Summary and Discussionsupporting
confidence: 86%
“…Recently, several works found interesting correlations between the outflow in narrow line region (NLR) and the mid-infrared emission(Zhang et al 2013;Hönig et al 2013). The outflows discussed here have much higher velocities than those in NLR.…”
mentioning
confidence: 99%
“…The sources in this sample have small contamination from host galaxies in their optical light, and their properties and data reduction are described in Dong et al (2011). Detailed analysis of narrow-line properties, especially the [O III]line, can be found in Zhang et al (2011Zhang et al ( , 2013aZhang et al ( , 2013b. The bolometric luminosity range of these sources is 10 44 -10 47 erg s −1…”
Section: Calibration Of the Kex Diagram Using Type 1 Agnsmentioning
confidence: 99%
“…However, Zhang et al (2013) found that the ratio of the [O III] wing and the bolometric luminosity is correlated with the mid-infrared covering factor. The wing is believed to rise from turbulent polar outflows in the inner narrow-line region (Peng et al 2014), and thus they propose that this indicates that a considerable fraction of the warm dust producing mid-infrared emission in AGN is likely embedded in polar outflows.…”
Section: Polar Dustmentioning
confidence: 95%
“…Such sources are plenty (see e.g. Zhang et al 2013;Lyu & Rieke 2018), and unfortunately we have no way of estimating the polar dust contribution without careful spectral energy distribution (SED) modelling or direct high-resolution mid-infrared observations of the emitting region, since such data is not available. Moreover, there are indications that high Eddington ratio sources, such as NLS1s, have a tendency to show more polar dust (Leftley et al 2019).…”
Section: Polar Dustmentioning
confidence: 99%